How Globalization and Economic Growth Affect Energy Consumption: Panel Data Analysis in the Sample of BRIC Countries - Dogan, Buhari; Deger, Osman (International Journal of Energy Economics and Policy, 2016)
This study analyzes the causality and cointegration correlation between the series using total energy consumption, economic growth, and globalization data of BRIC countries (Brazil, Russia, India, China) in 2000-2012 period. Unit roots of the series were extracted in empirical part in order to make them stationary. Then, Pedroni and Kao cointegration and Granger causality analysis panel were used. As a result of the cointegration analysis, it was observed that the series were cointegrated in the long term. On the other hand, causality analysis results suggested a unidirectional causality correlation from total energy consumption to economic growth, and another unidirectional causality correlation from globalization to economic growth. Lastly, no causality correlation between energy consumption and globalization was found. Keywords: Globalization, Economic Growth, Energy Consumption, BRIC. JEL Classifications: F60, O10, O13